Anglophobia in Fascist Italy - Pili, Jacopo (Book collections on Project MUSE., 2022)
Anglophobia in Fascist Italy traces the origins and development of anti-British sentiment in Fascist Italy, as Britain turned from being an ally in the First World War to an enemy in the Second. The book demonstrates that Fascist ideologues framed Britain as a stagnant and decaying country and the polar opposite of Fascism's new civilization, to the point that the regime's assessment of British political resolve and military might were distorted by ideological bias. The book offers a thorough analysis of diplomatic, military and journalistic sources and demonstrates that anti-British tropes had permeated Italy to a greater degree than was previously believed.